Organic anion transporters also mediate the drug-drug interaction between imipenem and cilastatin - Yanna Zhu; Xiaokui Huo; Changyuan Wang; Qiang Meng; Zhihao Liu; Huijun Sun; Aiping Tan; Xiaodong Ma; Jinyong Peng; Kexin Liu (Elsevier, 2020)
This study aimed to clarify that organic anion transporters (OATs) mediate the drug-drug interaction (DDI) between imipenem and cilastatin. After co-administration with imipenem, the plasma concentrations and the plasma concentration-time curve (AUC) of cilastatin were significantly increased, while renal clearance and cumulative urinary excretion of cilastatin were decreased. At the same time, imipenem significantly inhibited the uptake of cilastatin in rat kidney slices and in human OAT1 (hOAT1)-HEK293 and human OAT3 (hOAT3)-HEK293 cells. Probenecid, p-aminohippurate, and benzylpenicillin inhibited the uptake of imipenem and cilastatin in rat kidney slices and in hOAT1- and hOAT3-HEK 293 cells, respectively. The uptakes of imipenem and cilastatin in hOAT1- and hOAT3-HEK 293 cells were significantly higher than that in mock-HEK-293 cells. Moreover, the Km values of cilastatin were increased in the presence of imipenem with unchanged Vmax, indicating that imipenem inhibited the uptake of cilastatin in a competitive manner. When imipenem and cilastatin were co-administered, the level of imipenem was higher compared with imipenem alone both in vivo and in vitro. But, cilastatin significantly inhibited the uptake of imipenem when dehydropeptidase-1 (DPEP1) was silenced by RNAi technology in hOAT1- and hOAT3-HEK 293 cells. In conclusion, imipenem and cilastatin are the substrates of OAT1 and OAT3. OAT1 and OAT3 mediate the DDI between imipenem and cilastatin. Meanwhile, cilastatin also reduces the hydrolysis of imipenem by inhibiting the uptake of imipenem mediated by OAT1 and OAT3 in the kidney as a complement. Keywords: Imipenem/cilastatin, Renal dipeptidase, Organic anion transporters, Drug-drug interaction